Understanding Choices: Product Reviews And Customer Services As Determinants Of Online Purchase Decisions - Ananto Krisna Wardhana; Rachmat Fadly; Kurniawan Prambudi Utomo; Riris Lestiowati (UNIVED Press, 2024)
The aim of this research is to determine the influence of product and customer service reviews on purchasing decisions on online sites, how much each variable is related to each other, while the research method uses Stata Statistics 14 and quantitative descriptive, by testing statistical data in the form of good data processing. primary and secondary by taking a sample of 20 respondents consisting of customers who have or have made purchasing decisions online by conducting interviews, field observations (field research) with the method of distributing questionnaires directly, so that the research results show that product review variables and service influence Customers' online purchasing decisions have a significant positive value, both partially and simultaneously influencing online purchasing decisions